Audit Tingkat Keamanan Sistem Informasi Akademik Menggunakan Framework Cobit 5 - Nurwaida, An-Nisa Aina; Akbar, Yopi Hidayatul (Masoem University, 2024)
The Indonesian Institute of Cooperative Management (IKOPIN) uses an information system and system security to manage academic data, so that employee services to students can run effectively and efficiently. To find out the extent to which it is effective and efficient measurement system using the COBIT framework 5 in domain by IKOPIN APO (Align, Plan and Organize) and DSS (Delivery, Service and Support). To help the flow of information systems security audit process, the collection of data by doing observation, interviews, EG (Enterprise Goals) with IT mapping (ITRG Related Goals) generates the domains APO13, DSS01, DSS02, DSS03, DSS04, DSS05 and DSS06, determine determination, questionnaires, capability level analysis with APO and DSS domains starting from level 1 (Performed Process), level 2 (Managed Process), level 3 (Established Process ), level 4 (Predictable Process) and level 5 (Optimizing Process). From the results of the academic information systems security audit using COBIT Framework 5 in IKOPIN obtained a level of process capability 1.71 rounded to 2 with a gap of 1.28 rounded to 1, then the value was concluded that academic information system security is measured at the level of managed process.